122k views
5 votes
What is the product?

(x − 3)(2x2 − 5x + 1)

2x3 − x2 + 16x + 3
2x3 − 11x2 + 16x + 3
2x3 − 11x2 + 16x − 3
2x3 − x2 + 16x − 3

2 Answers

4 votes

Answer:

The product is 2x³ - 11x² + 16x - 3 ⇒ 3rd answer

Explanation:

* Lets explain how to find the product of binomial by trinomial

- If (ax² ± bx ± c) and (dx ± e) are trinomial and binomial, where

a , b , c , d , e are constant, their product is:

# Multiply (ax²) by (dx) ⇒ 1st term in the trinomial and 1st term in the

binomial

# Multiply (ax²) by (e) ⇒ 1st term in the trinomial and 2nd term in

the binomial

# Multiply (bx) by (dx) ⇒ 2nd term the trinomial and 1st term in

the binomial

# Multiply (bx) by (e) ⇒ 2nd term in the trinomial and 2nd term in the binomial

# Multiply (c) by (dx) ⇒ 3rd term in the trinomial and 1st term in

the binomial

# Multiply (c) by (e) ⇒ 3rd term the trinomial and 2nd term in

the binomial

# (ax² ± bx ± c)(dx ± e) = adx³ ± aex² ± bdx² ± bex ± cdx ± ce

- Add the terms aex² and bdx² because they are like terms

- Add the terms bex and cdx because they are like terms

* Now lets solve the problem

∵ The binomial is (x - 3) and the trinomial is (2x² - 5x + 1)

∴ (x)(2x²) = 2x³

∵ (x)(-5x) = -5x²

∵ (x)(1) = x

∵ (-3)(2x²) = -6x²

∵ (-3)(-5x) = 15x

∵ (-3)(1) = -3

∴ (x - 3)(2x² - 5x + 1) = 2x³ + -5x² + x + -6x² + 15x + -3

- Add the like terms

∵ -5x² and -6x² are like term

∴ Their sum is -11x²

∵ x and 15 x are like terms

∴ Their sum = 16x

∴ (x - 3)(2x² - 5x + 1) = 2x³ - 11x² + 16x - 3

* The product is 2x³ - 11x² + 16x - 3

User Sleeplessnerd
by
5.5k points
4 votes

Answer:

Third option: 2x^3-11x^2+16x-3

Explanation:

The product to be found is:


(x-3)(2x^2-5x+1)

Distributive property will be used for the product:


x(2x^2-5x+1)-3(2x^2-5x+1)\\

Multiplication will give us:


=2x^3-5x^2+x-6x^2+15x-3\\Combining\ alike\ terms\\=2x^3-5x^2-6x^2+x+15x-3\\=2x^3-11x^2+16x-3

The product is: 2x^3-11x^2+16x-3

Hence, third option is the correct answer ..

User Ajith Gopi
by
5.2k points